A novel gluconeogenic route enables efficient use of erythritol in zoonotic Brucella - Lázaro-Antón, Leticia; Veiga-da-Cunha, Maria; Elizalde-Bielsa, Aitor; Chevalier, Nathalie; Conde-Álvarez, Raquel; Iriarte, Maite; Letesson, Jean Jacques; Moriyón, Ignacio; Van Schaftingen, Emile; Zúñiga-Ripa, Amaia (Frontiers in Veterinary Science, 2024)
Brucellosis is a worldwide extended zoonosis caused by pathogens of the genus Brucella. While most B. abortus, B. melitensis and B. suis biovars grow slowly in complex media, they multiply intensely in livestock genitals and placenta indicating high metabolic capacities. Mutant analyses in vitro and in infection models emphasize that erythritol (abundant in placenta and genitals) is a preferred substrate of brucellae, and suggest hexoses, pentoses and gluconeogenic substrates use in host cells. While Brucella sugar and erythritol catabolic pathways are known, growth on 3-4 carbon substrates persists in Fbp-and GlpX-deleted mutants, the canonical gluconeogenic fructose 1,6-bisphosphate (F1,6bP) bisphosphatases. Exploiting B. suis biovar 5 prototrophic and fast-growing properties, we show that gluconeogenesis requires fructose-bisphosphate aldolase (Fba), the existence of a novel broad substrate bisphosphatase (Bbp) active on sedoheptulose 1,7-bisphosphate (S1,7bP), F1,6bP and other phosphorylated substrates, that Brucella Fbp unexpectedly acts on S1,7bP and F1,6bP, and that, while active in B. abortus and B. melitensis, GlpX is disabled in B. suis biovar 5. Thus, two Fba-dependent reactions (dihydroxyacetone-phosphate + glyceraldehyde 3-phosphate ⇌ F1,6bP; and dihydroxyacetone-phosphate + erythrose 4-phosphate ⇌ S1,7bP) can respectively yield fructose 6-phosphate and sedoheptulose 7-phosphate for classical gluconeogenesis and the Pentose Phosphate Shunt (PPS), the latter reaction opening a new gluconeogenic route. Since erythritol generates the PPS-intermediate erythrose 4-phosphate, and the Fba/Fbp-Bbp route predicts sedoheptulose 7-phosphate generation from erythrose 4phosphate, we re-examined the erythritol connections with PPS. Growth on erythritol required transaldolase or the Fba/Fbp-Bbp pathway, strongly suggesting that Fba/Fbp-Bbp works as a PPS entry for both erythritol and gluconeogenic substrates in Brucella. We propose that, by increasing erythritol channeling into PPS through these peculiar routes, brucellae proliferate in livestock genitals and placenta in the high numbers that cause abortion and infertility, and make brucellosis highly contagious. These findings could be the basis for developing attenuated brucellosis vaccines safer in pregnant animals